Estrogen‐related receptor α is involved in angiogenesis and skeletal muscle revascularization in hindlimb ischemia. Issue 5 (31st March 2021) - Sopariwala, Danesh H.; Likhite, Neah; Pei, Gungsheng; Haroon, Fnu; Lin, Lisa; Yadav, Vikas; Zhao, Zhongming; Narkar, Vihang A.
Abstract: Skeletal muscle ischemia is a major consequence of peripheral arterial disease (PAD) or critical limb ischemia (CLI). Although therapeutic options for resolving muscle ischemia in PAD/CLI are limited, the issue is compounded by poor understanding of the mechanisms driving muscle vascularization. We found that nuclear receptor estrogen‐related receptor alpha (ERRα) expression is induced in murine skeletal muscle by hindlimb ischemia (HLI), and in cultured myotubes by hypoxia, suggesting a potential role for ERRα in ischemic response. To test this, we generated skeletal muscle‐specific ERRα transgenic (TG) mice. In these mice, ERRα drives myofiber type switch from glycolytic type IIB to oxidative type IIA/IIX myofibers, which are typically associated with more vascular supply in muscle. Indeed, RNA sequencing and functional enrichment analysis of TG muscle revealed that "paracrine angiogenesis" is the top‐ranked transcriptional program activated by ERRα in the skeletal muscle. Immunohistochemistry and angiography showed that ERRα overexpression increases baseline capillarity, arterioles and non‐leaky blood vessel formation in the skeletal muscles. Moreover, ERRα overexpression facilitates ischemic neo‐angiogenesis and perfusion recovery in hindlimb musculature of mice subjected to HLI. Therefore, ERRα is a hypoxia inducible nuclear receptor that is involved in skeletal muscle angiogenesis and could be potentially targeted for treating PAD/CLI.